Somatometric profiles of successful male professional heavyweight boxers - Fiala, V.; Zywiczynski, P.; Turecek, P.; Wacewicz, S. (International Journal of Sports Science & Coaching, 2025)
Body mass is the most important predictor of success in fighting between conspecifics, with the heavier individual winning most fights. For this reason, the opponents in combat sports are usually weight-matched. The exception is the heavyweight division, which has no weight limit. Elite heavyweight athletes may cluster around an unknown global heavyweight optimum or compete at an individually specific optimal weight. We used comprehensive data (taken from boxrec.com) on bout outcomes for active male professional heavyweight boxers and Bayesian logistic regressions to explore the association between anthropometric predictors and the probability of winning. We identified the population-level optimum weight for heavyweight boxers at around 110 kg. The effects of age and height on the probability of winning were, however, much stronger than the effect of weight. Changing division during a boxer's professional career also affected performance: heavyweight athletes who during their professional careers also fought in lower weight classes were 19.9% [31.1-5.6%] less likely to win a bout in the heavyweight class. The study points to the importance of anthropometric measures for long-term success in professional heavyweight boxing and suggests a cut-off point, at which on average the marginal benefits of being a heavier boxer drop to 0.